ANALISIS TINGKAT PENDIDIKAN ORANG TUA, MOTIVASI BELAJAR, DAN KEMAMPUAN PEMECAHAN MASALAH TERHADAP HASIL BELAJAR MATEMATIKA - Sukendra, I Komang; Yuliastini, Ni Komang Sri (LP2M IKIP PGRI Bali, 2019)
This study aims to determine and analyze the relationship between parents' level of education, learning motivation, and problem solving abilities towards mathematics learning outcomes. The type of research used is qualitative (descriptive). Subjects used by students of class XI Natural Sciences in the city of Denpasar. The study was conducted at the State High School and private class XI Science Year 2018/2019 in Denpasar City. Implementation This research began in February until August 2019. Data analysis used multiple regression analysis, Pearson Product Moment Correlation (PPM), and the coefficient values ??were received. Based on the results of research and data analysis it can be concluded in this study are: (1) There is a relationship between the level of parental education on mathematics learning outcomes. (2) There is a relationship between students' learning motivation and learning outcomes. (3) There is a relationship between problem-solving abilities and mathematics learning outcomes (4) There is a simultaneous relationship between parents' level of education, learning motivation, and problem-solving abilities towards mathematics learning outcomes of XI high school students in Denpasar in the 2018/2019 Academic Year. Problem solving is influenced by the level of parental education and learning motivation which ultimately increases the learning outcomes of students' mathematics.